The Efficiency of Rural Infrastructure - Water Supply in Rural Areas of Transition - Johannes Sauer (European Regional Science Association (ERSA), 2003)
The provision of adequate infrastructure capital is crucial for the economic development and transition of rural areas in the former command economies of Central and Eastern Europe. Nevertheless, the commonly held perception of water and sewerage companies in economies of transition is, that the operational and financial performance is poor, revenue generation is inadequate and services are not provided in an efficient and cost-effective way. The objectives of this research project are therefore: -to analyse the relative efficiency of rural water suppliers in economies of transition and to identify and evaluate the relevant cost factors, -to analyse the effects of institutional infrastructure funding on the individual firm's efficiency and the implications for the national as well as EU-structural policy, -to formulate suggestions for the design of an optimal infrastructure policy with respect to rural water supplying systems in rural areas of EU-accession countries. First indicators with respect to economic performance were formulated on the basis of a preliminary data set of water suppliers in rural areas of East and West Germany. The data set is completed by a launched questionnaire distributed among 750 rural suppliers in Germany and Poland as well as by referring to existing statistics. Estimation models for the application of a stochastic frontier analysis were formulated and the problem of separate production stages and its implications for modelling and estimation were considered. Future research will focus on the completion of the cross-sectional data set and the estimation of a stochastic efficiency frontier as well as testing the hypothesis of separability with respect to rural water production and provision. Finally the empirical significance of institutional as well as transition variables included in the model has to be explained. This by referring to the institutional setting of infrastructure policy on the sub-national, national and supra-national scale. KEYWORDS: rural water supply, economic transition, efficiency measurement, stochastic frontier analysis, infrastructural policy
Keywords: 330